Optimal use of indicators and statistical methods in dealing with financial statements : (The Ministry of Electricity us a case study) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
Statistical numerical indicators are a powerful tool for analyzing life phenomena for which general or specialized data are available. Financial statements are one of those phenomena that researchers specializing in the financial aspect are interested in for several purposes, including professional and academic analysis as well as the possibility of making investment decisions. The importance of statistical numerical indicators in financial statements lies in converting numbers into information that can be interpreted and analyzed according to the analytical method used, including statistical methods that result in numerical indicators that can contribute to analyzing and interpreting the phenomenon under study. This research aims to employ indicators and statistical methods, whichever is compatible with the phenomenon, to benefit from them in academic and professional fields. Statistical methods were used to interpret the phenomenon of archived financial figures as periodic outputs of the Ministry of Electricity to identify the progress of the phenomenon statistically, with the aim of adopting them in the strategic aspect of sustainable work in that ministry. It became clear that there is a possibility of extracting statistical indicators in several fields and axes that can be relied upon at the research or professional level.